Strike the Rock and There Shall Come Water Climate Changes, Water Resources and History of the Lands of the Bible - Issar, Arie S. (SpringerBriefs in Geography,, 2014)
This book presents an update and revision of the book Water Shall Flow from the Rock - Hydrogeology and Climate in the Lands of the Bible by A. Issar, published by Springer-Verlag in 1990. The enormous quantity and quality of new data added since 1990 called for a thorough update. Another reason for this work is the better understanding achieved since the initial book was published about the role which climate plays in shaping the history of the Lands of the Bible. Albeit the fact that the impact of climate change was touched upon rather widely in the first book, still, without interweaving the new data and understanding, the picture would have remained partial.